A kind of foamed concrete based on graphite tailings and its production process
Through the combination of graphite tailings and modified resin, the overall mesh structure of foam concrete is formed, which solves the problems of poor mechanical properties and general anti-seepage effects of foam concrete, and significantly improves its mechanical properties and water resistance.
Patent Information
- Application Number
- CN202410397484.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-03
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-04-03
AI Technical Summary
At this stage, the mechanical properties of foam concrete are poor and the impermeability resistance is average.
Using the foam concrete production process based on graphite tailings, the modified resin is prepared by reaction of raw materials such as eugenol, epoxychlorohydrin, etc., and blended with modified fillers, cement and other materials to form silicone segments and sulfonic acid groups. The mesh molecules enhance hydrophobicity and calcium ion complexing ability, combine graphite tailings to promote calcium hydroxide consumption and C-S-H gel generation, forming an overall mesh structure.
It significantly improves the mechanical properties and water resistance of foam concrete, and enhances durability and compressive strength.
Smart Images

Figure GDA0004865938610000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foamed concrete preparation, and in particular to foamed concrete based on graphite tailings and a production process thereof. Background Art
[0002] With the acceleration of urbanization and the improvement of people's quality of life, the total energy consumption of buildings has increased year by year. The application of insulation materials for exterior wall insulation and roof insulation in the construction industry has increased year by year. At present, my country's building insulation materials are mainly divided into organic materials and inorganic materials. Organic insulation materials have a variety of insulation forms and excellent insulation performance, so they are more used in engineering. Organic insulation materials have the characteristics of light weight, high strength, excellent construction, and low thermal conductivity, including foamed polystyrene boards, extruded polystyrene boards, rigid polyurethane boards, and phenolic resin boards. Although organic insulation materials have many advantages, their characteristics such as easy aging, toxicity, poor durability, and flammability cannot be ignored. Inorganic insulation materials are usually made of inorganic materials as raw materials. They are safe and non-flammable, have good anti-aging properties, are energy-saving and environmentally friendly, but some materials have low strength and high water absorption, which affects their normal use. Summary of the invention
[0003] The purpose of the present invention is to provide a foamed concrete based on graphite tailings and a production process thereof, which solves the problems that the mechanical properties of the foamed concrete at present are poor and the anti-seepage effect is general.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A production process of foamed concrete based on graphite tailings specifically comprises the following steps:
[0006] Step A1: Eugenol, epichlorohydrin and DMF are mixed evenly, stirred at a speed of 150-200 r / min and a temperature of 100-110° C., benzyltrimethylammonium chloride is added, reacted for 2-3 hours, cooled to 80-85° C., sodium hydroxide solution is added, and reacted for 4-6 hours to obtain intermediate 1; intermediate 1, ethyl acrylate, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid are mixed evenly, stirred at a speed of 150-200 r / min and a temperature of 40-45° C., potassium persulfate is added, heated to 70-80° C., and reacted for 1-1.5 hours to obtain a strengthener;
[0007] Step A2: diphenyldichlorosilane and deionized water are mixed, stirred for 10-15 minutes at a speed of 200-300 r / min and a temperature of 60-70° C., concentrated sulfuric acid and 1,1,3,3-tetramethyldisiloxane are added, and the reaction is carried out for 4-6 hours, and the pH is adjusted to neutral to obtain terminal hydrogen polysiloxane, and the terminal hydrogen polysiloxane, epoxybutene and DMF are mixed uniformly, stirred at a speed of 150-200 r / min and a temperature of 50-60° C., and chloroplatinic acid is added, and the reaction is carried out for 10-15 hours to obtain a modified resin;
[0008] Step A3: uniformly mix the modified resin, the reinforcing agent and the acetone to obtain a modified resin emulsion, weigh the following raw materials in parts by weight: 2500-2700 parts of cement, 800-850 parts of fly ash, 300-350 parts of modified filler, 500-550 parts of silica fume, 150-200 parts of slag, 250-300 parts of graphite tailings, 80-90 parts of modified resin emulsion, 25-30 parts of curing agent, 60-65 parts of foaming agent and 850-900 parts of water, uniformly mix the raw materials and perform foaming and curing to obtain foamed concrete.
[0009] Furthermore, the dosage ratio of eugenol, epichlorohydrin, benzyltrimethylammonium chloride and sodium hydroxide solution in step A1 is 100 mmol:100 mmol:1.3 g:50 mL, the mass fraction of sodium hydroxide solution is 20%, the mass ratio of intermediate 1, ethyl acrylate, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid is 2:8:1:1, and the dosage of potassium persulfate is 1% of the mass of intermediate 1.
[0010] Furthermore, the amount ratio of diphenyldichlorosilane, deionized water and 1,1,3,3-tetramethyldisiloxane described in step A2 is 2mmo l:15mL:1mmo l, the amount of concentrated sulfuric acid is 1% of the mass of diphenyldichlorosilane, the molar ratio of terminal hydrogen polysiloxane and epoxybutene is 1:2, and the amount of chloroplatinic acid is 1‰ of the mass of terminal hydrogen polysiloxane.
[0011] Furthermore, the usage ratio of the modified resin, the reinforcing agent and the acetone in step A3 is 10 g: 1 g: 40 mL.
[0012] Further, the modified filler is prepared by the following steps:
[0013] Step B1: dispersing basalt fiber in anhydrous ethanol, stirring and adding γ-methacryloxypropyltrimethoxysilane and deionized water at a speed of 200-300 r / min and a temperature of 30-40° C., reacting for 3-5 hours, filtering and drying to obtain pretreated basalt fiber, and uniformly mixing the pretreated basalt fiber, ethyl acrylate and acrylic acid, stirring and adding potassium persulfate at a speed of 150-200 r / min and a temperature of 40-45° C., heating to 70-80° C., reacting for 1-1.5 hours, and obtaining modified basalt fiber;
[0014] Step B2: Disperse the modified basalt fiber in DMF, add γ-aminopropyltrimethoxysilane and dicyclohexylcarbodiimide, react for 3-5 hours at a speed of 150-200 r / min and a temperature of 30-40° C. to obtain a precursor, dissolve 4-formylphenylboric acid in DMF, add ammonium sulfate, stir and add γ-aminopropyltriethoxysilane at a speed of 200-300 r / min and a temperature of 40-50° C., and react for 4-6 hours to obtain a modifier;
[0015] Step B3: The precursor, the modifier, γ-glycidyloxypropyltrimethoxysilane and DMF are uniformly mixed, and deionized water is added under stirring at a speed of 150-200 r / min and a temperature of 60-65° C., and the mixture is reacted for 10-15 hours, and then the temperature is lowered to 20-25° C., and ammonium fluoride is added and reacted for 20-25 hours to obtain a modified precursor;
[0016] Step B4: Evenly mix hexagonal boron nitride, urea and deionized water, grind for 10-15 hours, filter and remove the filtrate, disperse the substrate in DMF, stir and add ethylene oxide at a speed of 200-300r / min, a temperature of 40-50°C, and a pH value of 8-9, and react for 4-6 hours to obtain modified boron nitride, evenly mix the modified precursor, modified boron nitride and DMF, ultrasonicate and add boron trichloride at a frequency of 20-30kHz and a temperature of 30-40°C, and react for 3-5 hours to obtain a modified filler.
[0017] Furthermore, the amount of γ-methacryloxypropyltrimethoxysilane in step B1 is 3% of the mass of the basalt fiber, the mass ratio of the pretreated basalt fiber, ethyl acrylate and acrylic acid is 1:12:5, and the amount of potassium persulfate is 0.1% of the mass of ethyl acrylate.
[0018] Furthermore, the molar ratio of the carboxyl group on the surface of the modified basalt fiber described in step B2, γ-aminopropyltrimethoxysilane and dicyclohexylcarbodiimide is 1:1:1.1, the molar ratio of 4-formylphenylboric acid and γ-aminopropyltriethoxysilane is 1:1, and the amount of ammonium sulfate used is 1% of the mass of 4-formylphenylboric acid.
[0019] Furthermore, the amount ratio of the precursor, modifier, γ-glycidyloxypropyltrimethoxysilane, deionized water and ammonium fluoride in step B3 is 100 mg: 5 g: 1 mL: 10 mL: 0.3 g.
[0020] Furthermore, the dosage ratio of hexagonal boron nitride, urea, deionized water and ethylene oxide in step B4 is 1g:30g:30mL:5mL, the mass ratio of modified precursor and modified boron nitride is 1:8, and the dosage of boron trichloride is 0.5% of the mass of modified precursor.
[0021] Beneficial effects of the present invention: A foamed concrete based on graphite tailings prepared by the present invention comprises the following raw materials in parts by weight: cement, fly ash, modified filler, silica fume, slag, graphite tailings, modified resin emulsion, curing agent, foaming agent and water; the modified resin emulsion reacts with eugenol and epichlorohydrin as raw materials, so that the hydroxyl group on the eugenol reacts with the epoxy group on the epichlorohydrin, and then the ring is closed under the action of sodium hydroxide to obtain an intermediate 1; the intermediate 1, ethyl acrylate, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid are polymerized to obtain a reinforcing agent; diphenyldichlorosilane is hydrolyzed, and then polymerized with 1,1,3,3-tetramethyldisiloxane to obtain a terminal hydrogen polysiloxane; the terminal hydrogen polysiloxane The alkylene and epoxybutene react to make the Si-H on the terminal hydrogen polysiloxane react with the double bond on the epoxybutene to obtain a modified resin. The modified resin, the reinforcing agent and acetone are mixed to obtain a modified resin emulsion. During the raw material blending process, the curing agent reacts with the modified resin and the reinforcing agent to form a grid molecule containing an organic silicon segment, which can enhance the hydrophobicity of the foamed concrete. At the same time, the grid molecule contains sulfonic acid groups and carboxyl groups, which can complex with calcium ions, thereby reducing the precipitation of calcium ions. The addition of graphite tailings can promote the consumption of calcium hydroxide inside the concrete and the formation of CSH gel, which crosses with the grid molecules to form an overall grid structure, so that the various raw materials of the concrete form a whole. When subjected to external forces, The modified filler is treated with γ-methacryloxypropyltrimethoxysilane with basalt fiber as raw material to make double bonds grafted on the surface to obtain pretreated basalt fiber, polymerize the pretreated basalt fiber, ethyl acrylate and acrylic acid to form polyacrylate on the surface to obtain modified basalt fiber, dehydrate the modified basalt fiber and γ-aminopropyltrimethoxysilane to make siloxane groups grafted on the surface, react 4-formylphenylboronic acid with γ-aminopropyltriethoxysilane to make the aldehyde group on the 4-formylphenylboronic acid react with the amino group on the γ-aminopropyltriethoxysilane to obtain a modifier, and mix the precursor, the modifier and γ-glycidyloxypropyl Trimethoxysilane is hydrolyzed and condensed to form a cage-type silsesquioxane on the surface of the precursor, and the cage-type silsesquioxane contains epoxy groups and boric acid groups. The hexagonal boron nitride is treated with urea to graft amino groups on the surface, and then reacted with ethylene oxide to react the amino groups and epoxy groups to form hydroxyl groups. The modified precursor and the modified boron nitride are reacted to react the boric acid groups on the surface of the modified precursor and the hydroxyl groups on the modified boron nitride to form a borate ester structure to obtain a modified filler. The modified filler contains epoxy groups that can participate in the cross-linking and curing of the modified resin and the reinforcing agent. At the same time, the core-shell structure can enhance the mechanical properties of the foamed concrete. The basalt fiber is coated with multiple layers to reduce the aging rate of the basalt fiber and improve the durability of the concrete. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1
[0024] A production process of foamed concrete based on graphite tailings specifically comprises the following steps:
[0025] Step A1: Eugenol, epichlorohydrin and DMF are mixed evenly, stirred at a speed of 150 r / min and a temperature of 100° C., benzyltrimethylammonium chloride is added, reacted for 2 hours, cooled to 80° C., sodium hydroxide solution is added, and reacted for 4 hours to obtain intermediate 1; intermediate 1, ethyl acrylate, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid are mixed evenly, stirred at a speed of 150 r / min and a temperature of 40° C., potassium persulfate is added, heated to 70° C., and reacted for 1 hour to obtain a strengthener;
[0026] Step A2: diphenyldichlorosilane and deionized water are mixed, stirred for 10 minutes at a speed of 200 r / min and a temperature of 60°C, concentrated sulfuric acid and 1,1,3,3-tetramethyldisiloxane are added, and the reaction is carried out for 4 hours, and the pH is adjusted to neutral to obtain terminal hydrogen polysiloxane, terminal hydrogen polysiloxane, epoxybutene and DMF are mixed uniformly, stirred at a speed of 150 r / min and a temperature of 50°C, chloroplatinic acid is added, and the reaction is carried out for 10 hours to obtain a modified resin;
[0027] Step A3: The modified resin, the reinforcing agent and the acetone are mixed uniformly to prepare a modified resin emulsion, and the following raw materials are weighed in parts by weight: 2500 parts of cement, 800 parts of fly ash, 300 parts of modified filler, 500 parts of silica fume, 150 parts of slag, 250 parts of graphite tailings, 80 parts of modified resin emulsion, 25 parts of curing agent, 60 parts of foaming agent and 850 parts of water, and the raw materials are mixed uniformly and foamed and cured to prepare foamed concrete.
[0028] The amount ratio of eugenol, epichlorohydrin, benzyltrimethylammonium chloride and sodium hydroxide solution described in step A1 is 100mmo l:100mmo l:1.3g:50mL, the mass fraction of sodium hydroxide solution is 20%, the mass ratio of intermediate 1, ethyl acrylate, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid is 2:8:1:1, and the amount of potassium persulfate is 1% of the mass of intermediate 1.
[0029] The amount ratio of diphenyldichlorosilane, deionized water and 1,1,3,3-tetramethyldisiloxane described in step A2 is 2mmo l:15mL:1mmo l, the amount of concentrated sulfuric acid is 1% of the mass of diphenyldichlorosilane, the molar ratio of terminal hydrogen polysiloxane and epoxybutene is 1:2, and the amount of chloroplatinic acid is 1‰ of the mass of terminal hydrogen polysiloxane.
[0030] The amount ratio of the modified resin, the reinforcing agent and the acetone described in step A3 is 10g:1g:40mL, the cement model is 42.5R, the fly ash is Class I fly ash, the particle size of the modified filler is 1mm, the particle size of the silica ash is 0.5μm, the slag is S95 grade granulated blast furnace slag, the particle size of the graphite tailings is 0.075mm, the curing agent is curing agent F0705, and the foaming agent is animal protein foaming agent FP30.
[0031] The modified filler is prepared by the following steps:
[0032] Step B1: dispersing basalt fiber in anhydrous ethanol, stirring and adding γ-methacryloxypropyltrimethoxysilane and deionized water at a speed of 200 r / min and a temperature of 30°C, reacting for 3 hours, filtering and drying to obtain pretreated basalt fiber, and uniformly mixing the pretreated basalt fiber, ethyl acrylate and acrylic acid, stirring and adding potassium persulfate at a speed of 150 r / min and a temperature of 40°C, heating to 70°C, and reacting for 1 hour to obtain modified basalt fiber;
[0033] Step B2: Disperse the modified basalt fiber in DMF, add γ-aminopropyltrimethoxysilane and dicyclohexylcarbodiimide, react for 3 hours at a speed of 150 r / min and a temperature of 30° C. to obtain a precursor, dissolve 4-formylphenylboric acid in DMF, add ammonium sulfate, stir and add γ-aminopropyltriethoxysilane at a speed of 200 r / min and a temperature of 40° C., and react for 4 hours to obtain a modifier;
[0034] Step B3: The precursor, the modifier, γ-glycidyloxypropyltrimethoxysilane and DMF were mixed evenly, stirred and deionized water was added at a speed of 150 r / min and a temperature of 60° C., and the mixture was reacted for 10 h. The mixture was then cooled to 20° C., ammonium fluoride was added, and the mixture was reacted for 20 h to obtain a modified precursor;
[0035] Step B4: Mix hexagonal boron nitride, urea and deionized water evenly, grind for 10 hours, filter and remove the filtrate, disperse the substrate in DMF, stir and add ethylene oxide at a speed of 200 r / min, a temperature of 40°C, and a pH value of 8, and react for 4 hours to obtain modified boron nitride. Mix the modified precursor, modified boron nitride and DMF evenly, ultrasonicate and add boron trichloride at a frequency of 20 kHz and a temperature of 30°C, and react for 3 hours to obtain a modified filler.
[0036] The amount of γ-methacryloxypropyltrimethoxysilane used in step B1 is 3% of the mass of basalt fiber, the mass ratio of pretreated basalt fiber, ethyl acrylate and acrylic acid is 1:12:5, and the amount of potassium persulfate used is 0.1% of the mass of ethyl acrylate.
[0037] The molar ratio of carboxyl, γ-aminopropyltrimethoxysilane and dicyclohexylcarbodiimide on the surface of the modified basalt fiber described in step B2 is 1:1:1. The molar ratio of 1,4-formylphenylboric acid and γ-aminopropyltriethoxysilane is 1:1, and the amount of ammonium sulfate used is 1% of the mass of 4-formylphenylboric acid.
[0038] The amount ratio of the precursor, modifier, γ-glycidyloxypropyltrimethoxysilane, deionized water and ammonium fluoride described in step B3 is 100 mg: 5 g: 1 mL: 10 mL: 0.3 g.
[0039] The dosage ratio of hexagonal boron nitride, urea, deionized water and ethylene oxide in step B4 is 1g:30g:30mL:5mL, the mass ratio of modified precursor and modified boron nitride is 1:8, and the dosage of boron trichloride is 0.5% of the mass of modified precursor.
[0040] Example 2
[0041] A production process of foamed concrete based on graphite tailings specifically comprises the following steps:
[0042] Step A1: Eugenol, epichlorohydrin and DMF are mixed evenly, stirred at a speed of 150 r / min and a temperature of 105° C., benzyltrimethylammonium chloride is added, reacted for 3 hours, cooled to 80° C., sodium hydroxide solution is added, and reacted for 5 hours to obtain intermediate 1; intermediate 1, ethyl acrylate, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid are mixed evenly, stirred at a speed of 150 r / min and a temperature of 45° C., potassium persulfate is added, heated to 75° C., and reacted for 1.5 hours to obtain a strengthener;
[0043] Step A2: diphenyldichlorosilane and deionized water are mixed, stirred for 15 minutes at a speed of 200 r / min and a temperature of 65° C., concentrated sulfuric acid and 1,1,3,3-tetramethyldisiloxane are added, and the reaction is carried out for 5 hours, and the pH is adjusted to neutral to obtain terminal hydrogen polysiloxane, and the terminal hydrogen polysiloxane, epoxybutene and DMF are mixed uniformly, stirred and chloroplatinic acid is added at a speed of 150 r / min and a temperature of 55° C., and the reaction is carried out for 15 hours to obtain a modified resin;
[0044] Step A3: The modified resin, the reinforcing agent and the acetone are mixed uniformly to prepare a modified resin emulsion, and the following raw materials are weighed in parts by weight: 2600 parts of cement, 830 parts of fly ash, 330 parts of modified filler, 530 parts of silica fume, 180 parts of slag, 280 parts of graphite tailings, 85 parts of modified resin emulsion, 28 parts of curing agent, 63 parts of foaming agent and 880 parts of water. The raw materials are mixed uniformly and foamed and cured to prepare foamed concrete.
[0045] The amount ratio of eugenol, epichlorohydrin, benzyltrimethylammonium chloride and sodium hydroxide solution described in step A1 is 100mmo l:100mmo l:1.3g:50mL, the mass fraction of sodium hydroxide solution is 20%, the mass ratio of intermediate 1, ethyl acrylate, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid is 2:8:1:1, and the amount of potassium persulfate is 1% of the mass of intermediate 1.
[0046] The amount ratio of diphenyldichlorosilane, deionized water and 1,1,3,3-tetramethyldisiloxane described in step A2 is 2mmo l:15mL:1mmo l, the amount of concentrated sulfuric acid is 1% of the mass of diphenyldichlorosilane, the molar ratio of terminal hydrogen polysiloxane and epoxybutene is 1:2, and the amount of chloroplatinic acid is 1‰ of the mass of terminal hydrogen polysiloxane.
[0047] The amount ratio of the modified resin, the reinforcing agent and the acetone described in step A3 is 10g:1g:40mL, the cement model is 42.5R, the fly ash is Class I fly ash, the particle size of the modified filler is 1mm, the particle size of the silica ash is 0.5μm, the slag is S95 grade granulated blast furnace slag, the particle size of the graphite tailings is 0.075mm, the curing agent is curing agent 8530, and the foaming agent is animal protein foaming agent FP30.
[0048] The modified filler is prepared by the following steps:
[0049] Step B1: dispersing basalt fiber in anhydrous ethanol, stirring and adding γ-methacryloxypropyltrimethoxysilane and deionized water at a speed of 200 r / min and a temperature of 35°C, reacting for 4 hours, filtering and drying to obtain pretreated basalt fiber, and uniformly mixing the pretreated basalt fiber, ethyl acrylate and acrylic acid, stirring and adding potassium persulfate at a speed of 150 r / min and a temperature of 45°C, heating to 75°C, and reacting for 1.5 hours to obtain modified basalt fiber;
[0050] Step B2: Disperse the modified basalt fiber in DMF, add γ-aminopropyltrimethoxysilane and dicyclohexylcarbodiimide, react for 4 hours at a speed of 150 r / min and a temperature of 35° C. to obtain a precursor, dissolve 4-formylphenylboric acid in DMF, add ammonium sulfate, stir and add γ-aminopropyltriethoxysilane at a speed of 200 r / min and a temperature of 45° C., and react for 5 hours to obtain a modifier;
[0051] Step B3: The precursor, the modifier, γ-glycidyloxypropyltrimethoxysilane and DMF were mixed evenly, stirred and deionized water was added at a speed of 200 r / min and a temperature of 60° C., and the mixture was reacted for 10 h, then cooled to 25° C., ammonium fluoride was added, and the mixture was reacted for 20 h to obtain a modified precursor;
[0052] Step B4: Mix hexagonal boron nitride, urea and deionized water evenly, grind for 15 hours, filter and remove the filtrate, disperse the substrate in DMF, stir and add ethylene oxide at a speed of 200 r / min, a temperature of 45°C, and a pH value of 8, and react for 5 hours to obtain modified boron nitride. Mix the modified precursor, modified boron nitride and DMF evenly, ultrasonicate and add boron trichloride at a frequency of 25 kHz and a temperature of 35°C, and react for 4 hours to obtain a modified filler.
[0053] The amount of γ-methacryloxypropyltrimethoxysilane used in step B1 is 3% of the mass of basalt fiber, the mass ratio of pretreated basalt fiber, ethyl acrylate and acrylic acid is 1:12:5, and the amount of potassium persulfate used is 0.1% of the mass of ethyl acrylate.
[0054] The molar ratio of carboxyl, γ-aminopropyltrimethoxysilane and dicyclohexylcarbodiimide on the surface of the modified basalt fiber described in step B2 is 1:1:1. The molar ratio of 1,4-formylphenylboric acid and γ-aminopropyltriethoxysilane is 1:1, and the amount of ammonium sulfate used is 1% of the mass of 4-formylphenylboric acid.
[0055] The amount ratio of the precursor, modifier, γ-glycidyloxypropyltrimethoxysilane, deionized water and ammonium fluoride described in step B3 is 100 mg: 5 g: 1 mL: 10 mL: 0.3 g.
[0056] The dosage ratio of hexagonal boron nitride, urea, deionized water and ethylene oxide in step B4 is 1g:30g:30mL:5mL, the mass ratio of modified precursor and modified boron nitride is 1:8, and the dosage of boron trichloride is 0.5% of the mass of modified precursor.
[0057] Example 3
[0058] A production process of foamed concrete based on graphite tailings specifically comprises the following steps:
[0059] Step A1: Eugenol, epichlorohydrin and DMF are mixed evenly, stirred at a speed of 200 r / min and a temperature of 110° C., benzyltrimethylammonium chloride is added, reacted for 3 hours, cooled to 85° C., sodium hydroxide solution is added, and reacted for 6 hours to obtain intermediate 1; intermediate 1, ethyl acrylate, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid are mixed evenly, stirred at a speed of 200 r / min and a temperature of 45° C., potassium persulfate is added, heated to 80° C., and reacted for 1.5 hours to obtain a strengthener;
[0060] Step A2: diphenyldichlorosilane and deionized water are mixed, stirred for 15 minutes at a speed of 300 r / min and a temperature of 70°C, concentrated sulfuric acid and 1,1,3,3-tetramethyldisiloxane are added, and the reaction is carried out for 6 hours, and the pH is adjusted to neutral to obtain terminal hydrogen polysiloxane, terminal hydrogen polysiloxane, epoxybutene and DMF are mixed uniformly, stirred at a speed of 200 r / min and a temperature of 60°C, chloroplatinic acid is added, and the reaction is carried out for 15 hours to obtain a modified resin;
[0061] Step A3: The modified resin, the reinforcing agent and the acetone are mixed uniformly to prepare a modified resin emulsion, and the following raw materials are weighed in parts by weight: 2700 parts of cement, 850 parts of fly ash, 350 parts of modified filler, 550 parts of silica fume, 200 parts of slag, 300 parts of graphite tailings, 90 parts of modified resin emulsion, 30 parts of curing agent, 65 parts of foaming agent and 900 parts of water. The raw materials are mixed uniformly and foamed and cured to prepare foamed concrete.
[0062] The amount ratio of eugenol, epichlorohydrin, benzyltrimethylammonium chloride and sodium hydroxide solution described in step A1 is 100mmo l:100mmo l:1.3g:50mL, the mass fraction of sodium hydroxide solution is 20%, the mass ratio of intermediate 1, ethyl acrylate, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid is 2:8:1:1, and the amount of potassium persulfate is 1% of the mass of intermediate 1.
[0063] The amount ratio of diphenyldichlorosilane, deionized water and 1,1,3,3-tetramethyldisiloxane described in step A2 is 2mmo l:15mL:1mmo l, the amount of concentrated sulfuric acid is 1% of the mass of diphenyldichlorosilane, the molar ratio of terminal hydrogen polysiloxane and epoxybutene is 1:2, and the amount of chloroplatinic acid is 1‰ of the mass of terminal hydrogen polysiloxane.
[0064] The amount ratio of the modified resin, the reinforcing agent and the acetone described in step A3 is 10g:1g:40mL, the cement model is 42.5R, the fly ash is Class I fly ash, the particle size of the modified filler is 1mm, the particle size of the silica ash is 0.5μm, the slag is S95 grade granulated blast furnace slag, the particle size of the graphite tailings is 0.075mm, the curing agent is curing agent 8530, and the foaming agent is plant protein foaming agent FP40.
[0065] The modified filler is prepared by the following steps:
[0066] Step B1: dispersing basalt fiber in anhydrous ethanol, stirring and adding γ-methacryloxypropyltrimethoxysilane and deionized water at a speed of 300 r / min and a temperature of 40°C, reacting for 5 hours, filtering and drying to obtain pretreated basalt fiber, and uniformly mixing the pretreated basalt fiber, ethyl acrylate and acrylic acid, stirring and adding potassium persulfate at a speed of 200 r / min and a temperature of 45°C, heating to 80°C, and reacting for 1.5 hours to obtain modified basalt fiber;
[0067] Step B2: Disperse the modified basalt fiber in DMF, add γ-aminopropyltrimethoxysilane and dicyclohexylcarbodiimide, react for 5 hours at a speed of 200 r / min and a temperature of 40°C to obtain a precursor, dissolve 4-formylphenylboric acid in DMF, add ammonium sulfate, stir and add γ-aminopropyltriethoxysilane at a speed of 300 r / min and a temperature of 50°C, and react for 6 hours to obtain a modifier;
[0068] Step B3: The precursor, the modifier, γ-glycidyloxypropyltrimethoxysilane and DMF were mixed evenly, stirred and deionized water was added at a speed of 200 r / min and a temperature of 65° C., and the mixture was reacted for 15 h. The mixture was then cooled to 25° C., ammonium fluoride was added, and the mixture was reacted for 25 h to obtain a modified precursor;
[0069] Step B4: Mix hexagonal boron nitride, urea and deionized water evenly, grind for 15 hours, filter and remove the filtrate, disperse the substrate in DMF, stir and add ethylene oxide at a speed of 300 r / min, a temperature of 50°C, and a pH value of 9, and react for 6 hours to obtain modified boron nitride. Mix the modified precursor, modified boron nitride and DMF evenly, ultrasonicate and add boron trichloride at a frequency of 30 kHz and a temperature of 40°C, and react for 5 hours to obtain a modified filler.
[0070] The amount of γ-methacryloxypropyltrimethoxysilane used in step B1 is 3% of the mass of basalt fiber, the mass ratio of pretreated basalt fiber, ethyl acrylate and acrylic acid is 1:12:5, and the amount of potassium persulfate used is 0.1% of the mass of ethyl acrylate.
[0071] The molar ratio of carboxyl, γ-aminopropyltrimethoxysilane and dicyclohexylcarbodiimide on the surface of the modified basalt fiber described in step B2 is 1:1:1. The molar ratio of 1,4-formylphenylboric acid and γ-aminopropyltriethoxysilane is 1:1, and the amount of ammonium sulfate used is 1% of the mass of 4-formylphenylboric acid.
[0072] The amount ratio of the precursor, modifier, γ-glycidyloxypropyltrimethoxysilane, deionized water and ammonium fluoride described in step B3 is 100 mg: 5 g: 1 mL: 10 mL: 0.3 g.
[0073] The dosage ratio of hexagonal boron nitride, urea, deionized water and ethylene oxide in step B4 is 1g:30g:30mL:5mL, the mass ratio of modified precursor and modified boron nitride is 1:8, and the dosage of boron trichloride is 0.5% of the mass of modified precursor.
[0074] Comparative Example 1
[0075] Compared with Example 1, no reinforcing agent was added in this comparative example, and the remaining steps were the same.
[0076] Comparative Example 2
[0077] Compared with Example 1, no modified resin emulsion was added in this comparative example, and the remaining steps were the same.
[0078] Comparative Example 3
[0079] Compared with Example 1, this comparative example uses basalt fiber instead of modified filler, and the other steps are the same.
[0080] Comparative Example 4
[0081] Compared with Example 1, this comparative example did not add γ-glycidyloxypropyltrimethoxysilane, and the remaining steps were the same.
[0082] Comparative Example 5
[0083] Compared with Example 1, this comparative example uses a modified precursor instead of a modified filler, and the remaining steps are the same.
[0084] The foamed concrete obtained in Examples 1-3 and Comparative Examples 1-5 was made into samples of 100mm×100mm×100mm and 100mm×100mm×400mm and cured for 28 days. The flexural strength and compressive strength were tested in accordance with the standard of GB / T11969-2008. The sample of 70mm×80mm×30mm was placed in a digital SS-1.5 mortar permeameter with an initial pressure of 0.2MPa. The pressure was maintained for 2h. If there was no water penetration, the pressure was increased to 0.3MPa. Thereafter, the pressure was increased by 0.1MPa every 1h until water seepage appeared in the sample. The water pressure was recorded. The test results are shown in the following table.
[0085]
[0086] It can be seen from the above table that the present application has good mechanical strength and water resistance.
[0087] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A production process of foamed concrete based on graphite tailings, characterized in that: The specific steps include: Step A1: eugenol, epichlorohydrin and DMF are mixed and stirred, benzyltrimethylammonium chloride is added, reacted, cooled and sodium hydroxide solution is added, reacted to obtain intermediate 1, intermediate 1, ethyl olefinate, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid are mixed and stirred, potassium persulfate is added, heated and reacted to obtain a fortifier; Step A2: After mixing and stirring diphenyldichlorosilane and deionized water, concentrated sulfuric acid and 1,1,3,3-tetramethyldisiloxane are added, and after reacting, the pH is adjusted to neutral to obtain terminal hydrogen polysiloxane, and the terminal hydrogen polysiloxane, epoxybutene and DMF are mixed and stirred, and chloroplatinic acid is added to react to obtain a modified resin; Step A3: uniformly mix the modified resin, the reinforcing agent and the acetone to obtain a modified resin emulsion, weigh the following raw materials in parts by weight: 2500-2700 parts of cement, 800-850 parts of fly ash, 300-350 parts of modified filler, 500-550 parts of silica fume, 150-200 parts of slag, 250-300 parts of graphite tailings, 80-90 parts of modified resin emulsion, 25-30 parts of curing agent, 60-65 parts of foaming agent and 850-900 parts of water, uniformly mix the raw materials and perform foaming and curing to obtain foamed concrete.
2. A production process for foamed concrete based on graphite tailings according to claim 1, characterized in that: The amount ratio of eugenol, epichlorohydrin, benzyltrimethylammonium chloride and sodium hydroxide solution in step A1 is 100 mmol:100 mmol:1.3 g:50 mL, and the mass ratio of intermediate 1, ethyl acrylate, 2-acrylamide-2-methylpropanesulfonic acid and acrylic acid is 2:8:1:
1.
3. The production process of foamed concrete based on graphite tailings according to claim 1, characterized in that: The amount ratio of diphenyldichlorosilane, deionized water and 1,1,3,3-tetramethyldisiloxane described in step A2 is 2mmol:15mL:1mmol, and the molar ratio of terminal hydrogen polysiloxane to epoxybutene is 1:
2.
4. The production process of foamed concrete based on graphite tailings according to claim 1, characterized in that: The amount ratio of the modified resin, the reinforcing agent and the acetone described in step A3 is 10g:1g:40mL.
5. The production process of foamed concrete based on graphite tailings according to claim 1, characterized in that: The modified filler is prepared by the following steps: Step B1: dispersing basalt fiber in anhydrous ethanol, stirring and adding γ-methacryloxypropyltrimethoxysilane and deionized water, reacting, filtering and drying to obtain pretreated basalt fiber, mixing the pretreated basalt fiber, ethyl acrylate and acrylic acid, stirring and adding potassium persulfate, heating and reacting to obtain modified basalt fiber; Step B2: Dispersing the modified basalt fiber in DMF, adding γ-aminopropyltrimethoxysilane and dicyclohexylcarbodiimide, reacting to obtain a precursor, dissolving 4-formylphenylboric acid in DMF, adding ammonium sulfate, stirring, and adding γ-aminopropyltriethoxysilane to react to obtain a modifier; Step B3: mixing and stirring the precursor, the modifier, γ-glycidyloxypropyltrimethoxysilane and DMF, adding deionized water, reacting, cooling and adding ammonium fluoride, reacting to obtain a modified precursor; Step B4: uniformly mix hexagonal boron nitride, urea and deionized water, grind and remove the filtrate by filtering, disperse the substrate in DMF, stir and add ethylene oxide to react to obtain modified boron nitride, ultrasonically mix the modified precursor, modified boron nitride and DMF and add boron trichloride to react to obtain a modified filler.
6. The production process of foamed concrete based on graphite tailings according to claim 5, characterized in that: The amount of γ-methacryloxypropyltrimethoxysilane used in step B1 is 3% of the mass of the basalt fiber, and the mass ratio of the pretreated basalt fiber, ethyl acrylate and acrylic acid is 1:12:
5.
7. The production process of foamed concrete based on graphite tailings according to claim 5, characterized in that: The molar ratio of the carboxyl group on the surface of the modified basalt fiber described in step B2, γ-aminopropyltrimethoxysilane and dicyclohexylcarbodiimide is 1:1:
1. The molar ratio of 1,4-formylphenylboronic acid and γ-aminopropyltriethoxysilane is 1:
1.
8. The production process of foamed concrete based on graphite tailings according to claim 5, characterized in that: The amount ratio of the precursor, modifier, γ-glycidyloxypropyltrimethoxysilane, deionized water and ammonium fluoride described in step B3 is 100 mg: 5 g: 1 mL: 10 mL: 0.3 g.
9. The production process of foamed concrete based on graphite tailings according to claim 5, characterized in that: The amount ratio of hexagonal boron nitride, urea, deionized water and ethylene oxide described in step B4 is 1g:30g:30mL:5mL, and the mass ratio of modified precursor to modified boron nitride is 1:
8.
10. A foamed concrete based on graphite tailings, characterized in that: Produced according to any one of the production processes described in claims 1-9.